Estudo do potencial de aplicação do resíduo de vidro laminado em argamassas de recuperação estrutural - Sauer, Aline Silva (2013)
The building is considered a major consumer of natural resources and generating waste. To minimize these impacts are new alternatives, among them the reuse of waste incorporated into building materials, which has been suggested as an appropriate way to preserve natural raw materials, save energy, reduce pollutant emissions and eliminate the costs of landfills. Studies on the incorporation of glass waste into cementitious matrices indicate the use of waste as a substitute for aggregates or agglomerates, the latter recommended, since in the fine particle (less than 75 μm) waste glass has high pozzolanic activity index, which can improve the mechanical properties of the cementitious matrices. This research aimed to evaluate the potential application of the windshield waste laminated glass in structural repair mortars, analyzing the influence of the variation in the percentage of replacement (by mass) of the cement for this waste (7%, 13%, 20% and 26%, and the reference mortar). Were analyzed in the fresh state properties, workability and density, and in the hardened state, compressive strength, modulus of elasticity, linear shrinkage and tensile strength, as well as analysis of water absorption by capillarity and microstructure. The mortar with 7% cement replacement by waste glass showed the best results regarding the mechanical performance, with values close to those found for the reference mortar. Already the permeability of the mortar tends to decrease with increasing level of substitution, where the mortar with 26% replacement showed lower values wicking. However, incorporation of glass waste to become more porous structure of mortar, but the size of pores was reduced with evidence of the formation of additional C-S-H by pozzolanic reactions. These results indicate a potential for the use of waste glass as a partial replacement of cement in mortar structural recovery, yet deserving, further research, especially with regard to the aspects of durability.